2009
DOI: 10.1017/s0022215109990508
|View full text |Cite
|
Sign up to set email alerts
|

Radiological balloon dilatation of post-treatment benign pharyngeal strictures

Abstract: Radiologically guided balloon dilatation is straightforward to perform and is well tolerated, but there is a small risk of perforation. Relief of symptoms is likely to be temporary, requiring multiple subsequent dilatations. A minority of patients will obtain no symptomatic relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Indeed, we encountered a single case with serious pharyngeal edema during the EBD procedure, and this patient had undergone radiotherapy for hypopharyngeal cancer. Second, technical success in EBD for pharyngo‐upper esophageal strictures does not necessarily lead to functional success, as described in previous studies . Actually, some degree of dysphagia remained, although improved, in the majority of our patients even after technically successful EBD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, we encountered a single case with serious pharyngeal edema during the EBD procedure, and this patient had undergone radiotherapy for hypopharyngeal cancer. Second, technical success in EBD for pharyngo‐upper esophageal strictures does not necessarily lead to functional success, as described in previous studies . Actually, some degree of dysphagia remained, although improved, in the majority of our patients even after technically successful EBD.…”
Section: Discussionsupporting
confidence: 63%
“…Second, technical success in EBD for pharyngo-upper esophageal strictures does not necessarily lead to functional success, as described in previous studies. 6,21 Actually, some degree of dysphagia remained, although improved, in the majority of our patients even after technically successful EBD. This is in contrast with cases of EBD for middlelower esophageal strictures in which the absence of dysphagia was achieved in the majority of patients treated with EBD.…”
Section: Ysphagia Is a Major Complication After Treatmentmentioning
confidence: 58%
“…The included studies are summarized in Table . All studies were retrospective, and most reported outcomes of standard anterograde dilations using bougie or balloon dilators with or without guidewires.…”
Section: Resultsmentioning
confidence: 99%
“…The average patient age was 60 (range 21–89) years, and there was a near 3:1 male predominance (232:87, 73%:27%) . Cancer staging and treatment data were reported variably (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation